Pendampingan Siswa SMP MBS Al-Amin Bojonegoro dalam Menulis Cerita Pendek dengan Menggunakan Metode Project-Based Learning - Cahyo Hasanudin; Ayu Fitrianingsih; Leli Nisfi Setiana; Rani Jayanti; Brillianing Pratiwi; Priyantoko Priyantoko (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The aims of this community service program is to provide assistance the students of SMP MBS Al Amin Bojonegoro in writing short stories using project-based learning. The method of this program is divided into three stages, namely initial stage, main stage, and final stage. In the initial stage, observation and interview are carried out. Moreover, it conducts problem analysis and literature review. In the main stage, the students are trained to write short stories by implementing project-based learning. In the final stage, monitoring and evaluation are carried out. In the end of this stage, students are given gifts. The conclusion of this community service program is the students of SMP MBS Al Amin Bojonegoro are able to write short stories easily when projectbased learning is implemented. This method helps students in describing the storyline based on their experiences in the boarding house. They starts to write it using the stages given.